The Medial Prefrontal Cortex and the Emergence of Self-Conscious Emotion in Adolescence - Somerville, Leah H.; Jones, Rebecca M.; Ruberry, Erika J.; Dyke, Jonathan P.; Glover, Gary; Casey, B. J. (Psychological Science, 2013)
In the present study, we examined the relationship between developmental modulation of socioaffective brain systems and adolescents’ preoccupation with social evaluation. Child, adolescent, and adult participants viewed cues indicating that a camera was alternately off, warming up, or projecting their image to a peer during the acquisition of behavioral-, autonomic-, and neural-response (functional MRI) data. Believing that a peer was actively watching them was sufficient to induce self-conscious emotion that rose in magnitude from childhood to adolescence and partially subsided into adulthood. Autonomic arousal was uniquely heightened in adolescents. These behavioral patterns were paralleled by emergent engagement of the medial prefrontal cortex (MPFC) and striatum-MPFC connectivity during adolescence, which are thought to promote motivated social behavior in adolescence. These findings demonstrate that adolescents’ self-consciousness is related to age-dependent sensitivity of brain systems critical to socioaffective processes. Further, unique interactions between the MPFC and striatum may provide a mechanism by which social-evaluation contexts influence adolescent behavior.